Regards croisés sur les mondes de l’autoportrait : le cas des artistes d’origine marocaine Hicham Benohoud, Mehdi-Georges Lahlou et Zakaria Ramhani - Pinto Ferretti, Alexia (Muséologies, 2018)
This article takes a contemporary look at the practice of self-portraiture by three artists from Morocco: Hicham Benohoud, Mehdi-Georges Lahlou and Zakaria Ramhani. The career trajectories of these creators illustrate the various dynamics of institutional opposition and integration mechanisms that belong to the new geographies of art, in the era of globalization. The article's goal is to investigate the manner in which individual, local and global concerns are expressed in their understanding of an imaginary projection of corporality. The works are studied through the lens of local characteristics particular to the artist's Maghreb-Muslim culture. In the first section, the artists' careers, in relation to their training and the places where they have exhibited their work, are presented in tandem with the paradoxes of globalization. It is thus specified that if the artists were trained primarily in the West or made their careers there to achieve international success, it can be attributed to a lack of support from the Moroccan artistic scene, but also to the difficult access to the international art world for artists coming from the art scenes of the Maghreb. In the second part, we postulate that the artists' self-portraits attest to the different issues related to Maghreb-Muslim culture, such as the current socio-political situation in Morocco and the Islamic ban on representation. Lastly, we maintain that these self-portraits are a wider reflection of the varied concerns that transcend the borders of the Maghreb, as the artists reflect on the meeting of the Eastern and Western worlds.